Developing Mathematics Teachers’ TPACK Competencies through Technology-Enhanced Learning Approaches - Orhani, Senad (DIROSAT: Journal of Education, Social Sciences & Humanities, 2026)
The ability of teachers to effectively integrate technology into the learning process has become essential for the development of students' competencies in STEM fields, especially in mathematics. The purpose of this study is to analyze the development of Technological Competencies, Pedagogical and Content Knowledge (TPACK) in mathematics teachers through Technology-Enhanced Learning (TEL). Effective integration of technology into teaching has become an essential component in teacher professional development and in improving the quality of learning in STEM fields. The study uses a mixed-methods approach, integrating quantitative data from a questionnaire with 52 teachers and qualitative data from eight semi-structured interviews. The results showed that teachers possess high levels of pedagogical and content knowledge, but technological competencies are still developing. Correlation analysis Pearson found a strong positive relationship between TEL use and TPACK level (r = .70, p < .01), while linear regression showed that TEL use explains 39% of the variance in TPACK development (β = 0.62, p < .001). On the other hand, qualitative data revealed that teachers perceive TEL as an approach that increases student motivation and engagement, although they encounter infrastructural barriers and a lack of consistent training. The study concludes that the systematic use of TEL positively influences the development of integrated TPACK competencies, promoting more interactive and reflective teaching. In conclusion, it is recommended to strengthen sustainable professional development policies, integrate training based on the TPACK model, and provide institutional support for the pedagogical use of technology in mathematics teaching.